Issues and Challenges of Third-party Logistics in China: Case studies combination on a SME, a large-scale international organization and a professional Third-party Logistics Company - gao, ang (2006)
With the fast development of globalization, China has to face a big pressure which is brought by international competition as the biggest invested market all over the world. Third-party logistics (TPL) industry brings a lot of benefits to global organizations. Likewise, it also provides a vast amount of opportunities to China as a powerful weapon to overcome the challenges of global competition. However, Chinese TPL is still at the starting stage of its development